Improving Counting Skills Assisted by The Jarimatika Method in Fifth Grade Elementary School Students - Widyanengrum, Novita; Ningrum, Dhelia Anggita; Arifin, Septiani Nuraini; Riswari, Lovika Ardana (Fakultas Tarbiyah dan Ilmu Keguruan, UIN Kiai Haji Achmad Siddiq Jember, 2023)
This study aims to improve students' multiplication counting skills in mathematics. The design of this study uses the Classroom Action Research (PTK) model which in its implementation uses 2 cycles. The independent variable in this study is the jarimatics method, with the dependent variable namely increasing numeracy skills. The population in this study were students at SD 2 Bategede, with a sample of 19 students. This research consisted of 2 cycles, which consisted of planning, implementing, monitoring, and reflecting. Learning is increased in cycle 2 if the indicators for cycle 1 have not been achieved. The collection and analysis of information is carried out on the results of the implementation of the study and partner observations. The results showed that the use of the jarimatics method could improve learning outcomes and changes in attitudes towards learning materials. In cycle I, the average was 69.47. Learning is increased in cycle 2 if the indicators in cycle 1 have not achieved learning success. Then after cycle II the average increase was 86.31. Thus, it is concluded that the use of the jarimatics method can improve learning outcomes and changes in student achievement in learning. Learning using the jarimatics method and other learning tools can make learning more active.